CD47-SIRPα Controls ADCC Killing of Primary T Cells by PMN Through a Combination of Trogocytosis and NADPH Oxidase Activation - Gondois-Rey, Françoise; Miller, Thomas; Laletin, Vladimir; Morelli, Xavier; Collette, Yves; Nunès, Jacques; Olive, Daniel (Frontiers in Immunology, 2022)
Immunotherapies targeting the “don’t eat me” myeloid checkpoint constituted by CD47 SIRPα interaction have promising clinical potential but are limited by toxicities associated with the destruction of non-tumor cells. These dose-limiting toxicities demonstrate the need to highlight the mechanisms of anti-CD47-SIRPα therapy effects on non-tumor CD47-bearing cells. Given the increased incidence of lymphopenia in patients receiving anti-CD47 antibodies, and the strong ADCC (Antibody-Dependent-Cellular-Cytotoxicity) effector function of Poly Morpho Nuclear Cells (PMNs), we investigated the behavior of primary PMNs cocultured with primary T cells in the presence of anti-CD47 mAbs. PMNs killed T cells in a CD47-mAb-dependent manner and at a remarkably potent PMN to T cell ratio of 1:1. The observed cytotoxicity was produced by a novel combination of both trogocytosis and a strong respiratory burst induced by classical ADCC and CD47-SIRPα checkpoint blockade. The complex effect of the CD47 blocking mAb could be recapitulated by combining its individual mechanistic elements: ADCC, SIRPα blockade and ROS induction. Although previous studies had concluded that disruption of SIRPα signaling in PMNs was limited to trogocytosis-specific cytotoxicity, our results suggest that SIRPα also tightly controls activation of NADPH oxidase, a function demonstrated during differentiation of immature PMNs but not so far in mature PMNs. Together, our results highlight the need to integrate PMNs in the development of molecules targeting the CD47-SIRPα immune checkpoint and to design agents able to enhance myeloid cells function while limiting adverse effects to healthy cells able to participate in the anti-tumor immune response.